Common Pitfalls in the Interpretation of Endocrine Tests - Alvarez-Payares, Jose C.; Bello-Simanca, Jesus David; De La Peña-Arrieta, Edwin De Jesus; Agamez-Gomez, Jose Emilio; Garcia-Rueda, Jhon Edwar; Rodriguez-Arrieta, Amilkar; Rodriguez-Arrieta, Luis Antonio (Frontiers in Endocrinology, 2021)
Endocrine tests are the cornerstone of diagnosing multiple diseases that primary care physicians are frequently faced with. Some of these tests can be affected by situations that affect the proper interpretation, leading to incorrect diagnoses and unnecessary treatment, such as the interference of biotin with thyroid function test, falsely elevated prolactin values in presence of macroprolactinemia or falsely normal due to the “hook effect” in macroprolactinomas. Recognizing these situations is essential for the clinician to make an adequate interpretation of these tests as well as an accurate diagnosis that guarantees the best outcomes for the patient.